The globular cluster system of the galaxy NGC 6876 - Ennis, Ana Inés (2017)
We present preliminary results of the deep photometric study of the elliptical galaxy NGC6876, located at the center of the Pavo group, and its globular cluster system. We use images obtained with the GMOS camera mounted on the Gemini South telescope, in the g' and i' bands, with the purpose of disentangling the evolutionary history of the galaxy on the basis of its characteristics.